The new annotated checklist of the wild bees of Europe (Hymenoptera: Anthophila) - Ghisbain, Guillaume; Rosa, Paolo; Bogusch, Petr; Flaminio, Simone; Divelec, Romain Le; Dorchin, Achik; Kasparek, Max; Kuhlmann, Michael; Litman, Jesse; Mignot, Maud; Müller, Andreas; Praz, Christophe; et al. (Zootaxa, 2023)
At a time when nature conservation has become essential to ensure the long-term sustainability of our environment, it is widely acknowledged that conservation actions must be implemented within a solid taxonomic framework. In preparation for the upcoming update of the IUCN Red List, we here update the European checklist of the wild bees (sensu the IUCN geographical framework). The original checklist, published in 2014, was revised for the first time in 2017. In the present revision, we add one genus, four subgenera and 67 species recently described, 40 species newly recorded since the latest revision (including two species that are not native to Europe), 26 species overlooked in the previous European checklists and 63 published synonymies. We provide original records for eight species previously unknown to the continent and, as original taxonomic acts, we provide three new synonyms, we consider two names as nomina nuda, ten names as nomina dubia, three as species inquirenda, synonymize three species and exclude 40 species from the previous checklist. Around a hundred other taxonomic changes and clarifications are also included and discussed. The present work revises the total number of genera for IUCN Europe to 77 and the total number of species to 2,138. In addition to specifying the taxonomic changes necessary to update the forthcoming Red List of European bees, we discuss the sampling and taxonomic biases that characterise research on the European bee fauna and highlight the growing importance of range expansions and species invasions.